WAKAMONO KOTOBA â€œMAJIâ€ DALAM KALIMAT PERCAKAPAN BAHASA JEPANG DITINJAU DARI SEGI SOSIOLINGUISTIK - Andini, Fatmawati; Isnaini, Zuli Laili; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed at affecting social factor and situation factor toword the using of maji in Japanese conversationâ€™s sentence. This research used qualitative approach and analyzed by William Labovâ€™s social factor theory and Fishmanâ€™s situation factor theory. The subject in this research was the word maji used in Japanese conversation sentences from Japanese dramas called Koinaka and Summer Nude. Data collectionâ€™s method was â€œsimakâ€ method and used â€œsimak bebas libat cakapâ€ technic and taking note method. Data analyseâ€™s method was â€œpadanâ€ method or â€œextralingual padanâ€ method and used â€œhubung banding menyamakanâ€ technic. The result shows that in social factor, the word maji often used by middle class people in every sector of works, and used by educated people or in process of education. The word maji used by people around adolescent to adult, when the listener around adolescent to elder. The word maji can be used by male or female. In situation factor, the word of maji often be used in informal conversation with various topics. Non-standard language variety often be used in conversation when using maji.Key Words: social factor, situation factor, wakamono kotoba, maji.